Plan de Mejoramiento para los Servicios Ofertados en la "QUINTA AIDITA" del Cantón Guano. - López Obregón, Oscar Santiago (2010)
The Inn “Quinta Aidita” during the time that have been on the market doesn’t have an improvement plan for tourism services offered, to contribute in the management of market, which was led to the wishes and needs of the tourists have not been fully satisfied. In the present investigations has used the prescriptive and experimental method as it has verified the quality of tourist services are there in The Inn “Quinta Aidita” to complete the improvement of these services through a survey of local tourists and employees in addition to direct interviews to the administrator. The interviews and survey, made know that The Inn “Quinta Aidita” , there are administrative failures by not having a structural and functional organization, therefore there is not designation of roles in the organization, there is not improvement strategies in the services offered, employees are unclear about their duties and they don’t have a motivation on the part of management, the tourists said that they like the tourist services offered by the Inn, but need to improve them.